The influence of airflow characteristics and accumulation grid velocity on the formation of a stone wool primary layer - Peternelj, Marko (Strojniški vestnik, 2017)
In this paper, the industrial process of stone wool primary layer formation has been investigated. The blow-away airflow, collecting chamber suction pressure, and peripheral velocity of collecting member effects on primary layer area density have been investigated. In total, 27 operating points have been measured by means of primary layer visualization. Computer-aided visualization has been carried out by two digital cameras. Each operating point was monitored at two locations: the first one at the beginning of fibre accumulation, forming the primary layer, and the secondary one at the end of the formation zone. The mass attenuation coefficient was calculated for each operating point and then used to calculate the primary layer area density. It was determined that primary layer bulk density distribution and primary layer texture are significantly influenced by accumulation grid peripheral velocity and blow-away airflow; however, suction pressure has a less pronounced effect on those characteristics. At the highest accumulation grid velocity and blow-away flow rate, the area density was 37 % lower than at the lowest grid velocity and blow-away flow, with a corresponding increase in a standard deviation of 750 %. Multiple regression models suggest very good agreement with the measured data (Rsup = 0.94 to 0.98).
Keywords: centrifuga; formiranje primarne plasti; mineralna volna; pnevmatski transport; vlakna; zbiralna komora